Diagnóstico de potencialidades turísticas del patrimonio religioso inmueble de la ciudad de Portoviejo - Bravo Sabando, Karla Vicenta (2023)
The objective of this research was to elaborate a diagnosis of the immovable religious heritage of the city of Portoviejo for the identification of its tourist potentialities, working from a non-experimental exploratory level with a qualitative and quantitative approach. First, a characterization of the heritage was carried out, which allowed the description of the study area from the political, architectural and cultural-tourist level, then interview questionnaires were applied to representatives of the INPC, archdiocesan administrator and the different priests of the canton, allowing the identification of seven religious infrastructures, which were subjected to an analysis of the historical, symbolic and social relationship. Afterwards, a matrix was applied to identify the capacities and attributes that the architectural assets have for the diversification of products and services, where two were determined with a high possibility and five with an emerging capacity. Finally, the design of strategies was carried out through the validation of nine experts, who met the requirements established in the methodology of García, et al. (2020) to be selected, the proposal consisted of 14 strategies of which 13 met more than 80% of acceptance and only one was invalidated, these demonstrated the importance of the design of this type of proposals aimed at the enhancement of the religious heritage, leading an organized management that allows the revaluation, conservation and safeguarding of the real estate, effectively promoting the appropriate local development by taking advantage of it through tourism activities.